Pelatihan Pemasaran untuk UMKM : Meningkatkan Daya Saing Produk melalui Branding dan Promosi di Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Andalusi, Ratih; Sulistiani, Sinta; Wulansari, Retno (Jurnal PKM Manajemen Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital component of Indonesia’s economic structure, particularly in rural areas. However, many MSME actors still face challenges in marketing their products effectively, especially in terms of branding and promotion. This community service (PKM) activity titled "Marketing Training for MSMEs: Enhancing Product Competitiveness through Branding and Promotion at Tajaul Karomah, Situ Gadung Village, Tangerang Regency" was carried out to address these issues. The main objective was to improve the marketing capabilities of MSME players in Situ Gadung by equipping them with knowledge and practical skills in branding and promotional strategies. The activity was implemented in April 2025 at Tajaul Karomah School in Situ Gadung Village and involved 12 lecturers from Pamulang University as facilitators. A total of 25 participants, including local community members and MSME actors, took part. The PKM was conducted in three stages: preparation, implementation, and reporting. Methods used included lectures, hands-on practice, group discussions, and Q&A sessions. The results showed a significant increase in participants’ understanding of branding techniques, promotional tools, and digital marketing strategies. Participants also demonstrated improved confidence in applying these methods to their businesses. Overall, the training successfully contributed to enhancing product competitiveness in the local MSME sector.